3y+9=y+3

Simple and best practice solution for 3y+9=y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+9=y+3 equation:


Simplifying
3y + 9 = y + 3

Reorder the terms:
9 + 3y = y + 3

Reorder the terms:
9 + 3y = 3 + y

Solving
9 + 3y = 3 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
9 + 3y + -1y = 3 + y + -1y

Combine like terms: 3y + -1y = 2y
9 + 2y = 3 + y + -1y

Combine like terms: y + -1y = 0
9 + 2y = 3 + 0
9 + 2y = 3

Add '-9' to each side of the equation.
9 + -9 + 2y = 3 + -9

Combine like terms: 9 + -9 = 0
0 + 2y = 3 + -9
2y = 3 + -9

Combine like terms: 3 + -9 = -6
2y = -6

Divide each side by '2'.
y = -3

Simplifying
y = -3

See similar equations:

| (x-2)(x+4)=x(x+3)-5x | | 180=(2x+2)+(3x+1) | | 3(4x+5)-2(3x-2)=3x+7 | | t*5-4=16 | | 20+3x-2=x^2-4x | | -4b=3(-4b)+7 | | 180=(8x)+x+90 | | 0.86(3.7-2.3x)=4.9 | | (7n-2)(5n-1)=0 | | 0.86(3.7-2.3x)=49 | | 30a^2+7a=0 | | (5v+7)(2+v)=0 | | g(-4b)=3(-4b)+7 | | 2x^3-8x^2-192x=0 | | 6cos+5tan=0 | | 5r+4r-9r= | | 6cisb+5tan=0 | | 2x=-10-2 | | 180=2x+76 | | 180=2x+76+(5x-2) | | 6(3x+5)-5(x-7)=39 | | c=6+5x | | 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= | | 2(8+6x)+2=4(4+3x)+2x | | 4a^3+12a^2-9a-27=0 | | 45+40a= |

Equations solver categories